PERFORMANCE OF BOTUMOPUTI VILLAGE APPARATUS TIBAWA DISTRICT OF GORONTALO REGENCY - Siswanto Luawo; Darman; Karlina Napu (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This research aims to find out the performance of botumoputi villageapparatus of Tibawa District of Gorontalo Regency, this type of research isdescriptive research with qualitative approach the type of data used isprimary data and secondary data with data sourced from observations,interviews and documentation. Informants in this study amounted to 5people who were botumoputi village apparatus.The results of this study show that the performance of the villageapparatus in community perception about the performance of the villageapparatus is quite good judging from the results of work, discipline,responsibility.In the completion of the task of the performance of the villageapparatus is quite good for the process, and also in terms of taking thedecision of the village government in establishing RAPBD, as well as theselection of the development of the village government refers to the rulesthat have been adhered to already good for the progress and development ofthe village.